2019
DOI: 10.3390/catal9080647
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Carriers and Non-Aqueous Solvents for Enzyme Immobilization

Abstract: Immobilization techniques are generally based on reusing enzymes in industrial applications to reduce costs and improve enzyme properties. These techniques have been developing for decades, and many methods for immobilizing enzymes have been designed. To find a better immobilization method, it is necessary to review the recently developed methods and have a clear overview of the advantages and limitations of each method. This review introduces the recently reported immobilization methods and discusses the impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 116 publications
(102 reference statements)
0
25
0
Order By: Relevance
“…As a result, they have attracted great interest as matrix materials for enzyme immobilization. [11][12][13][14][15][16][17][18][19][20][21][22][23] Various studies have shown that MCM-41 materials have a pore size of just 3.0 nm, and are thus limited to the immobilization of enzymes with small sizes. [15][16][17] Furthermore, despite their high surface areas (ca.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they have attracted great interest as matrix materials for enzyme immobilization. [11][12][13][14][15][16][17][18][19][20][21][22][23] Various studies have shown that MCM-41 materials have a pore size of just 3.0 nm, and are thus limited to the immobilization of enzymes with small sizes. [15][16][17] Furthermore, despite their high surface areas (ca.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the use of free xylanase is often hampered by its lack of reusability, high production costs, low enzymatic activity and high consumption. However, immobilized enzymes can be reused in multiple cycles to reduce the production costs and overcome such technical bottlenecks [9,10].…”
mentioning
confidence: 99%
“…The morphology of nanoscale supports has a great impact on the enhancement of enzyme activities and the stability of nanobiocatalysts ( Figure 2) [12]. Continuous efforts have yielded many nanostructured supports with various morphologies to provide a large surface area for increased enzyme loading and reduced diffusion resistance [21,79]. Many enzyme immobilization strategies have been developed in consideration of the optimal morphology of supports for minimizing the effect of conformation distortions and the deactivation of immobilized enzymes.…”
Section: Morphology Effect Of Nanoscale Supportmentioning
confidence: 99%
“…Nanobiocatalysts with increased enzyme activity can be obtained via either covalent binding, adsorption, entrapment, or encapsulation [5,6,14,15]. The structure of nanoscale supports, such as nanoparticles, nanowires, microspheres, metal-organic frameworks, and nanoflowers, has also drawn extensive attention in recent years [5,[16][17][18][19][20][21][22]. A great deal of effort has also been made to design nanostructured supports with a variety of components including noble metal (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation